Electrically tunable topological notch filter for THz integrated photonics - Gupta, Manoj (2023)
Electromagnetic filtering is essential for emerging integrated photonic technologies and widely adaptable processing of high-bandwidth signals. The conventional electro-optic modulator-based photonic approach for signal filtering at microwave frequencies cannot be implemented at terahertz (THz) frequencies due to the unavailability of the THz signal-driven optical modulator. Here, an electrically tunable on-chip THz photonic notch filter based on the topologically protected valley hall waveguide-cavity platform is demonstrated. The device shows a significantly large notch suppression depth of more than 20 dB with a return loss of 13 dB in the entire tuning range of notch frequency. The feedback control circuit enables precise control of the notch frequency shift with a minimum step size of 7 MHz. This work extends the application of topological photonic crystals in developing THz-integrated photonic devices for transformative technologies, including sixth-generation (6G) communication and high-resolution spectral sensing.